Open Reduction and Internal Fixation of a Fracture-dislocation of the Ankle - Yaniel Truffin Rodriguez; José Julio Requeiro Molina; Gerardo Águila Tejeda (Medisur)
Open reduction and internal fixation of the fracture-dislocation of the ankle with plates, screws and Kirschner wires is a well-defined treatment method. This paper presents the management of a fracture-dislocation of the right ankle in a 33-year-old female patient stabilized by using a one-third tubular plate, screws, and Kirschner wires with tension-band wires. Results were satisfactory.